Mitigating fluctuations of wind power generation using superconducting magnetic energy storage: A passivity-based approach (2019)
Abstract This paper presents the control of the active and reactive power of a superconducting magnetic energy storage (SMES) system for compensating fluctuations of a power system with high penetration of wind energy during extreme scenarios of wind gusts. The wind energy conversion system (WECS) is a Type-A turbine with squirrel cage induction generator (SCIG) and a capacitor bank. A passivity-based proportional-integral control (PI-PBC) is used that controls the power transfer of the SMES system to the power grid. The proposed controller is designed with two main objectives: First, to deliver (or absorb) a suitable active power to (or from) the power system, and second, to regulate the voltage of the WECS. The proposed PI-PBC guarantees asymptotically stability in closed-loop and exploits the advantages of the proportional-integral (PI) actions. Also, it presents a superior performance when it is compared to a conventional PI controller and a proportional feedback linearization controller. Simulation results carried-out in MATLAB/SIMULINK demonstrate the advantages of the proposed methodology. © 2019 IEEE.